Pottery in the Central Desert of Libya (Abhat Journal, 2023)
The pottery industry indicates the beginning of stability, the beginning of the cultivation and breeding of livestock, and pottery as a raw material is one of the most common types of archaeological finds, and scholars describe pottery since prehistoric times on the components of silt, burning and surface treatment, to what Al-Fakharani made of raw material decisions, and accordingly he did not Pottery is not only a means of dating, but it provides us with a lot of information about the economy and the distinctive and intellectual lifestyles. This research deals with pottery in the central desert as a survey study through which we seek to try to interrogate the few pottery fragments that were taken in different places of this geographical space. Thus, show the extent of the importance of the region and its role in the civilizational development of the entire region.  With the help of studies that were conducted in the encirclement regions such as Egypt Algeria and Sudan and making comparisons between them, and the study concluded that this region has influenced and was affected by neighboring civilizations during long historical periods that produced types of pottery in which several civilizations intermarried by virtue of its central location
Keywords: Neolithic; Middle Sahara; Corrugated pottery; Pointed pottery; Harouge